1993
DOI: 10.1038/clpt.1993.129
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects, pharmacokinetics, and converting enzyme inhibition of enalapril after morning versus evening administration

Abstract: The cardiovascular effects and pharmacokinetics of once-daily enalapril were studied after single-dose and subchronic treatment in eight patients with hypertension by use of ambulatory blood pressure monitoring. Enalapril, 10 mg, was given at either 7 AM or 7 PM in a randomized crossover design. In addition, inhibition of serum converting enzyme was studied. Subchronic treatment at 7 AM significantly reduced blood pressure during the day but was less effective at night. Subchronic dosing at 7 PM significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(44 citation statements)
references
References 12 publications
4
40
0
Order By: Relevance
“…Several crossover studies (morning vs evening dosing) have been published for both ACE inhibitors 82,89,[126][127][128] and AT 1 -receptor blockers. [129][130][131] They demonstrated that in contrast to morning dosing, evening dosing of ACE inhibitors such as benazepril, enalapril, and perindopril resulted in a more pronounced nightly drop.…”
Section: Ace Inhibitors and At 1 -Receptor Blockersmentioning
confidence: 99%
“…Several crossover studies (morning vs evening dosing) have been published for both ACE inhibitors 82,89,[126][127][128] and AT 1 -receptor blockers. [129][130][131] They demonstrated that in contrast to morning dosing, evening dosing of ACE inhibitors such as benazepril, enalapril, and perindopril resulted in a more pronounced nightly drop.…”
Section: Ace Inhibitors and At 1 -Receptor Blockersmentioning
confidence: 99%
“…T:P ratio data achieved with morning administration may not apply to night-time dosing. 21,[40][41][42] T:P ratio may not represent the ideal guide to management of hypertensive patients. Rather it helps to determine whether BP is normalised during both day and night and whether the excessive acute rises seen in hypertensive individuals have been suppressed.…”
Section: Resultsmentioning
confidence: 99%
“…However, previous studies using ABPM up to 48 hours including the second day of treatment showed for both the ␤-adrenoceptor-blocker atenolol 19 and the ACE-inhibitor enalapril 20 that though no significant BP reduction was observed after 20-24 hours after drug intake the effect reappeared the next day off therapy. Consequently, a reliable assess-ment of the duration of the antihypertensive effect cannot be provided by our study design with ABPM restricted to 24 hours.…”
Section: Discussionmentioning
confidence: 97%